What boundary conditions should we apply? Applications to tunneling and to the AECL Underground Research Laboratory - F. Tonon; B. Amadei (The Southern African Institute of Mining and Metallurgy, 2003)
Rock stress measurement is cast in the more general context of the determination of boundary conditions for rock engineering. A study on the effect of elastic anisotropy on underground excavations reveals that this effect is actually controlled by the imposed boundary conditions. Applications to tunneling and to the Underground Research Laboratory (URL), Canada, exemplify a procedure for boundary condition estimation formerly developed by the authors. The procedure displayed fast convergence despite the complex geometry, and the high degree of non-linearity of the models. In the URL application, the 3-D model was able to completely reproduce the complex measured stress pattern, and the 90° rotation of the principal in situ stresses with depth. In order to reliably estimate the boundary conditions reproducing the current in situ state of stress, response measurements of the rock mass to current disturbances are necessary as input data. La mesure des contraintes in situ tombe dans le domaine général de la détermination des conditions aux limites pour les problèmes de mécanique des roches. Une étude sur le rôle de l’anisotropie élastique sur les excavations souterraines montre que ce rôle est contrôlé par les conditions aux limites qui sont imposées. L’application aux tunnels et au Laboratoire Souterrain de Recherche (URL) au Canada, nous permet de présenter une méthode de détermination des conditions aux limites. La méthode converge rapidement bien que le géométrie soit complexe et que le problème soit non-linéaire. Pour le URL, le modèle 3D est capable de reproduire la distribution des contraintes qui ont été mesurées ainsi que la rotation de 90 degrés des contraintes in situ avec la profondeur. Afin de déterminer avec précision les conditions aux limites responsables pour la distribution actuelle des contraintes, la réponse du massif rocheux doit être connue et mesurée. In der Felsentechnik sind die Spannungsmessungen in Gestein an die Bestimmung der Randbedingungen gebunden. Eine Studie legt dar, dass der Effekt elastischer Anisotropie in unterirdischen Aushoehlungen von den Randbedingungen kontrolliert ist. Eine von den Authoren entwickelte Methode zur Bestimmung der Randbedingungen wird an Beispielen im Tunnelbau und im Underground Research Laboratory (URL) in Kanada illustriert. Auch bei komplexer Geometrie und einem hohen Grad an Nicht-Linearitaet zeigt diese Methode ein schnelles Konvergenzverhalten. Ein 3D-Model und dessen 90° Drehung der lokalen Hauptspannungen mit der Tiefe, kann bei einer URL Anwendung vollstaendig reproduziert werden. Um mit dieser Methode die Randbedingungen zuverlaessig abschaetzen zu koennen, werden der gegenwaertige lokale Spannungszustand sowie die Antwort des Gesteins und die resultierenden Stoerungen als Eingabedaten benoetigt.